2012
DOI: 10.1590/s1516-35982012000100023
|View full text |Cite
|
Sign up to set email alerts
|

Corn silage with and without enzyme-bacteria inoculants on performance, carcass characteristics and meat quality in feedlot finished crossbred bulls

Abstract: -Two height cuttings of corn silage with or without enzyme inoculants were evaluated for 68 days on performance, carcass characteristics, meat quality and chemical composition of the Longissimus muscle in crossbred bulls (F1 -½ Nellore vs. ½ Angus) finished in feedlot. Thirty-two 20-month-old bulls, with initial average weight of 374±25 kg, were kept in individual pens (10 m 2 ). Diets consisted of 50% roughage and 50% concentrate, with an expected 1.80 kg/day weight gain. The experimental design with four die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
2
13
1
2
Order By: Relevance
“…Mean DM conversion was approximately 6.2 kg of DM for 1 kg of BW gain and may be attributed to the genetic quality of animals (½ Angus vs ½ Nellore), their sexual condition (bulls) and the diet's high energy density (75% TDN). Usually, crossbred bulls fed on a high energy density diet have feed conversion of 7 kg of DM intake for 1 kg of BW gain (Fugita et al, 2012;Maggioni et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Mean DM conversion was approximately 6.2 kg of DM for 1 kg of BW gain and may be attributed to the genetic quality of animals (½ Angus vs ½ Nellore), their sexual condition (bulls) and the diet's high energy density (75% TDN). Usually, crossbred bulls fed on a high energy density diet have feed conversion of 7 kg of DM intake for 1 kg of BW gain (Fugita et al, 2012;Maggioni et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…An enzyme-bacterial inoculant acts in two forms in silage: whereas bacterial inoculants improve fermentation proile and increase lactic acid bacteria population, enzyme inoculants act on the cell wall and the available higher quantity of soluble compounds, with improvement in silage digestibility [44].…”
Section: Alternatives To Improve Intake and Digestibility Of Silagementioning
confidence: 99%
“…In support with our results, Ribeiro et al (2002) observed increases in KPH of crossbred bulls as concentrate level increased and a trend for increased backfat thickness as concentrate levels increased. Fugita et al (2012) in Nellore-Angus crossbred cattle fed 50% concentrate diet and Rodrigues et al (2013) in bullocks fed 75% concentrate diet compared to diet B. Concentrate fed heifers or steers had higher (P<0.01) fat thickness and KPH% than forage-fed heifers or steers as reported by Garmyn et al (2010) and Duckett et al (2013).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 82%